Getting to know you more featuring ... Assoc. Prof. Rr. Rushita Ismail / Rasaya Marimuthu - Marimuthu, Rasaya (Academy of Language Studies, 2022)
Could you kindly provide some details of yourself? Maybe a bit of your biodata, your involvement before working at UiTM, and also your work philosophy. Thank you Mr. Rasaya. I was born in Jelutong, Penang, to a beautiful couple of seven children and a year later came my brother. I went to Convent Butterworth primary and secondary schools in Butterworth. When I was offered to do TESOL in the USA after SPM, then I thought this is it. Teaching is my line then. Upon returning home I was posted to a school in my hometown, Balik Pulau. My first of three children was two years old at that time and he had the experience of growing up in a kampong environment before we moved to Selangor. It was a delightful teaching expe- rience for me at those schools in both states as I could see the differences between the urban and rural schools in issues regarding class management and parents’ involvement. Students, whoever and wherever they are, need the attention that could be given to them. I believe that when we have the chance to get connected with them, we should embrace the moments and make the most of them.